2021
DOI: 10.1039/d0gc03426f
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of a high-density aviation fuel using a polycarbonate

Abstract: A high-density cyclic hydrocarbon mixture was first synthesized by a one-pot transfer hydrodeoxygenation of a polycarbonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…[188,189] The current annual worldwide production of PC is around 6 million tons. [190] Polymers manufactured via polycondensation can be recycled more effortlessly than those made by other polymerization methods. [191] However, in the case of PC, the release of bisphenol A (BPA), which is a toxic compound and a known endocrine disruptor, may cause harm to humans and also to the environment.…”
Section: Polycarbonatementioning
confidence: 99%
“…[188,189] The current annual worldwide production of PC is around 6 million tons. [190] Polymers manufactured via polycondensation can be recycled more effortlessly than those made by other polymerization methods. [191] However, in the case of PC, the release of bisphenol A (BPA), which is a toxic compound and a known endocrine disruptor, may cause harm to humans and also to the environment.…”
Section: Polycarbonatementioning
confidence: 99%
“…Another one‐pot catalytic system for PC upcycling used Raney metals (e. g., Ni, Co, Fe, Cu) as the catalyst and isopropanol as both solvent and hydrogen donor, producing a mixture of C 6 –C 15 oxygenates and cycloalkanes (Figure 10). [65] Raney Ni was the most active among all Raney metals and afforded C 6 –C 15 oxygenates with a yield of more than 60 % after reaction at 463 K for 1 h. The yield of C 6 –C 15 cyclic hydrocarbons was about 31 %. A temperature up to 523 K promoted the hydrodeoxygenation of oxygenates into hydrocarbons, but hydrocarbons yield was only slightly enhanced.…”
Section: Liquid Hydrocarbonsmentioning
confidence: 96%
“…It has been reported that the two reactions can be conducted sequentially or in one-pot, depending on the solvents and catalysts that were applied in the system (Figure 10). [63][64][65] For instance, in a two-step process, PC underwent alcoholysis with methanol generated bisphenol A in a yield up to 90 % in the absence of any catalyst at 453 K. Then a dual catalyst composed of Pt/C and H-β catalyzed the subsequent hydrodeoxygenation of bisphenol A in 3 MPa H 2 at 413 K, affording jet fuel-range C 15 cycloalkanes with a high yield of 87 %. [63] The excellent performance of this dual catalyst is contributed to high activity of Pt/C for hydrogenation of the benzene ring in bisphenol A, and the relatively high pore size and acidity of H-β (compared to other zeolites such as HZSM-5 and MOR), which favored intermediates diffusion and promoted dehydration of hydroxy groups.…”
Section: Catalytic Conversion Of Plastics With Aromatic Monomers To J...mentioning
confidence: 99%
“…After several recycling cycles, PCs ends up in landfills or incineration. Several chemical processes of pyrolysis, hydrolysis, alcoholysis, and aqueous phase hydrodeoxygenation (APHDO) [27] have been reported regarding PC depolymerization and valorization.…”
Section: Polycarbonatementioning
confidence: 99%